How to draw Manga chibis in simple steps - Li, Yishan (kent Search Press, 2016)
A guide to drawing manga chibis--characters with exaggerated features who often play cute or villainous roles--with artistic exercises that provide step-by-step instructions on drawing, inking, and coloring techniques, along with tips on shape, anatomy, color, lighting, tools, and materials
2 13 14
Keywords: Comic books, strips, etc -- Technique